1970
DOI: 10.1021/ma60018a007
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Ferrocenylmethyl Acrylate and Ferrocenylmethyl Methacrylate. Characterization of Their Polymers and Their Polymeric Ferricinium Salts. Extention to Poly(ferrocenylethylene)

Abstract: Poly(ferrocenylmethyl acrylate), poly(ferrocenylmethyl methacrylate), and poly(ferrocenylethylene) have been prepared by AIBN-catalyzed, free-radical polymerization in benzene solution. Treatment of these polymers with strongly electron attracting compounds such as tetracyanoethylene, dichlorodicyanoquinone, and o-chloranil leads to poly(ferricinium) salts, or polymeric charge-transfer derivatives. The characterization of these polymers was carried out by kinetic studies, infrared, nuclear magnetic resonance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 0 publications
0
48
1
Order By: Relevance
“…[30] Incorporation of the ferrocene moiety into polymeric materials is possible by a variety of techniques including free radical polymerization of vinyl ferrocene [31] or ferrocene containing methacrylates, [32] the ring-opening polymerization of strained ferrocenophanes [33][34][35][36] or polycondensation of suitable ferrocene derivatives such as diols and dicarboxylic acids. [37,38] Ferrocene-containing polymers unify the electronic and magnetic properties of ferrocene itself with the facile immobilization of active centers and high functional density in polymers to generate new materials, for example in catalytic applications.…”
Section: Ferrocene-containing Polymersmentioning
confidence: 99%
“…[30] Incorporation of the ferrocene moiety into polymeric materials is possible by a variety of techniques including free radical polymerization of vinyl ferrocene [31] or ferrocene containing methacrylates, [32] the ring-opening polymerization of strained ferrocenophanes [33][34][35][36] or polycondensation of suitable ferrocene derivatives such as diols and dicarboxylic acids. [37,38] Ferrocene-containing polymers unify the electronic and magnetic properties of ferrocene itself with the facile immobilization of active centers and high functional density in polymers to generate new materials, for example in catalytic applications.…”
Section: Ferrocene-containing Polymersmentioning
confidence: 99%
“…[101][102][103][104][105] These polymers displayed a number of interesting physical and chemical properties. It was found, for example, that the presence of a ferrocene unit in the side chains of polymers increased their glass transition temperatures.…”
Section: Polymerization Of Olefin-functionalized Metallocenesmentioning
confidence: 99%
“…It was found, for example, that the presence of a ferrocene unit in the side chains of polymers increased their glass transition temperatures. [101] Wrighton has also reported that electrodes modified with polymers containing ferrocene or cobaltocene groups can be used to photoelectrochemically reduce halocarbons. [106] As well, a number of kinetic studies on the polymerization behavior of these organoiron monomers showed that they did not follow the same rate laws as organic monomers.…”
Section: Polymerization Of Olefin-functionalized Metallocenesmentioning
confidence: 99%
“…With enthusiastic efforts paid by polymer scientists, FcPs could be prepared by free radical, anionic, ringopening, cyclotrimerization and condensation polymerizations [18][19][20][21][22][23][24][25][26][27][28]. Most of these polymerization techniques, however, should be carried out under harsh reaction conditions and careful exclusion of moisture and oxygen is necessary, which greatly limit their applications.…”
Section: Introductionmentioning
confidence: 99%